Design and Development of an E-commerce Website as a Media for Dissemination Information and Product Marketing at CV Rahayu Barokah Gedongsari - Rossa, Assifah Salsabiilaa; Azizah, Azizah -; Ayuwardani, Mellasanti -; Nugroho, Jati - (Admisi dan Bisnis, 2024)
The development of information technology, especially the internet, is currently prosessing rapidly and has become a crucial medium for information dissemination and communication. The increasing number of internet users is driving the growth of e-commerce in Indonesia. CV Rahayu Barokah Gedongsari is an SME engaged in the production and sale of natural skin care products under the brand “Ralodex”. CV Rahayu Barokah Gedongsari still lacks information about its products and does not have a wide marketing rich. To address this issue, an informative e-commerce website is developed to introduce the brand “Ralodex” and expand its marketing reach. The objective of this research is to design an e-commerce website as a media for dissemination infromation, presenting detailed product information to introduce the brand expand its marketing reach. The methods used is developing this website is Waterfall method, which involves several stage: requirement analysis and definition, ayatem and software design, implementation and unit testing, integration and system testing, operation and maintenance. The outcome of this e-commerce website design is to provide ease of access for visitors from various devices, and it offers extensive product information, making it an effective online media for information dissemination with boarder marketing reach